Controls on structural styles along the deformation front of the Subandean zone of southern Bolivia - Rocha, Emilio (2015)
The Subandean zone of southern Bolivia is a typical thin-skinned fold and thrust belt with remarkable regularity in the geometry of the structures. However, when the structural geometry and evolution are analyzed in detail, it is verified that there are many deviations from such regularity. In this paper, special emphasis has been placed on analyzing those processes that could explain the along strike variations in structural styles of the deformation front. Particularly, the role that played the upper detachment level in the development of the different structural styles observed along the deformation front is analyzed herein. This analysis is focused on the development of overpressures, which may have been essential for the activation of the detachment level in the Devonian shales of the Los Monos Formation. To do this, we made a series of 1D petroleum system models at different locations along the deformation front. This analysis allowed to model primary gas generation and secondary cracking d processes that are related to overpressure occurrence, and therefore, to the efficiency of the upper detachment level. The models suggest a close relationship between thermal evolution of the foreland basin and generation of gas, with different structural styles observed at the deformation front. Thus, it was possible to divide the deformation front of the southern Subandean zone into two distinct segments. In the northern segment, where models suggest that gas generation and overpressures of the Los Monos Formation would be well developed, the existence of composite roof duplexes is verified. On the other hand, where the models suggest that generation of gas in the Los Monos Formation would be limited, the upper detachment level is not involved in the deformation, and the existence of fault bend fold structures is verified.